Analisis Load Balancing Berbasis Mikrotik Dalam Meningkatkan Kemampuan Server di Institut Shanti Bhuana - Andri Mikola; Azriel Christian Nurcahyo (Journal of Information Technology, 2022)
Abstract— With the development of technology, the number of new users in the field of technology will increase. Along with the development of technology, the ability in the internet network is also increasing, causing a traffic on the network to get worse. Load blanching can make the performance on the internet network more optimal and make the network traffic process more stable. Load Blancing configuration can be done on the Mikrotik server through the Winbox application media. The configuration process so that it becomes stable can be done with 2 ISPs so that the network is evenly distributed. With Load Balancing, it is not only about distributing equity on the network but also as a control and balancing on the web server. The process of testing traffic on the network we got a network speed of 17.6 Mbps, and it can be concluded that the internet network at the Shanti Bhuana Institute is classified as "Good".